The Effectiveness of the BTA Program in Improving the Ability to Read and Write the Qur'an at MTs Ma'arif NU 1 Sumbang - Abdurrozak, Jaja; Hanifah, Faza Ahna; Azizah, Isnaeni; Wulandari, Luthfia (DAS Institute, 2024)
This research will analyze the effectiveness and determine the obstacles and solutions in implementing the BTA program at MTs N 1 Sumbang. MTs Ma'arif NU 1 Sumbang is one of the private junior secondary education institutions in Banyumas, which is under the auspices of the Ministry of Religion. Reading and Writing the Al-Qur'an (BTA) is a mandatory program for grade 9. This research is qualitative research with descriptive methods, where data obtained from the field is described and presented in the form of written narratives. This qualitative research was chosen to describe and analyze in depth the phenomena related to the implementation of the BTA program at MTs Ma'arif NU 1 Sumbang. This research resulted that MTs Ma'arif NU Sumbang requires grade 9 students to carry out BTA every time they come home from school, namely 13.20-13.20 on Monday to Thursday. BTA was carried out with the usual courtesy, and then we tried to use a new approach using different methods, learning media, and duration. Obstacles that occur include students not paying attention, chatting alone, playing on their cellphones, or running away. Our solution is to approach the students and give them a warning. If they want to run away, the teacher will prevent them. Apart from that, they were also given motivation to be enthusiastic and were informed of the significance of the learning that would be carried out on that day. In 13 meetings, there were 16 children who we considered were able to continue from Iqro to al-Qur'an.